Porous resin molding
The development of a porous resin molded body using polyolefin resin with specific monomer ratios and tertiary carbons, combined with an inclined foaming method, addresses the challenge of creating a body with an inclined foam structure, achieving effective porosity change and planarity.
Patent Information
- Application Number
- JP2023172573
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
Existing technologies face challenges in creating a porous resin molded body with an inclined foam structure, where porosity changes in the thickness direction, due to difficulties in controlling bubble rate and maintaining flatness.
A porous resin molded body made from a polyolefin resin with a propylene fraction less than 14 mol% and 7 or more tertiary carbons per 1,000 carbons, utilizing an inclined foaming method where the foaming agent is impregnated and heated with a controlled temperature gradient to achieve an inclined foaming structure.
The solution enables the creation of a porous resin molded body with a well-established inclined foam structure, ensuring good planarity and effective porosity change in the thickness direction, while minimizing undulations and wrinkles.
Smart Images

Figure 2025063413000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous resin molded article having a porosity that changes gradually in the thickness direction. [Background technology]
[0002] For example, Patent Document 1 discloses a gradient foamed plastic sheet produced by dissolving a gas that is gaseous at room temperature and pressure into plastic under high temperature and pressure, exposing the plastic to an atmosphere under a pressure lower than the pressure at which the gas was dissolved, and then exposing both sides of the sheet to atmospheres of different temperatures. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-363324 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present inventors have made intensive studies focusing on such background art, and have come to the following findings. That is, in Patent Document 1, the sheet is foamed by the extrusion foaming method, and foaming occurs immediately after extrusion from the die, so that even if both sides of the sheet are exposed to atmospheres with different temperatures thereafter, it is difficult to change the foaming rate in a gradient manner, that is, it is difficult to increase the degree of gradient. Furthermore, Patent Document 1 shows an example in which the sheet is passed through temperature-controllable rolls to expose both sides of the sheet to atmospheres with different temperatures, but it is difficult to highly foam the sheet when sandwiched between the rolls. In addition, the bubbles formed in the sheet tend to be large and horizontally elongated in the extrusion direction (plane direction), and the foaming rate, i.e., the expansion rate of the material, is different on both sides of the sheet, which makes the sheet prone to undulations and wrinkles. For this reason, it is difficult to ensure flatness, and such defects as undulations and wrinkles become more pronounced when the sheet is highly foamed.
[0005] Therefore, in view of the above-mentioned background technology, the present inventors have conducted further intensive research in order to provide a porous resin molding using a polyolefin-based resin as a base resin and in which a gradient foam structure in which the porosity changes gradiently in the thickness direction is well formed, and as a result, have completed the present invention. [Means for solving the problem]
[0006] The gradient foamed molded article according to the present invention is a porous resin molded article in which the porosity changes gradiently in the thickness direction, and the base resin is a polyolefin-based resin, 13 The propylene fraction of the monomer unit ratio measured by CNMR is less than 14 mol%, 13 The number of tertiary carbon atoms as measured by CNMR is 7 or more per 1000 carbon atoms. Effect of the Invention
[0007] According to the present invention, it is possible to provide a porous resin molded body having a favorable gradient foam structure in which the porosity changes gradiently in the thickness direction. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is an explanatory diagram illustrating a porous resin molded body according to an embodiment of the present invention. [Diagram 2] 1A to 1C are explanatory diagrams showing a production example of a porous resin molded body according to an embodiment of the present invention. [Diagram 3] 1 shows cross-sectional CT images of Example 1. [Figure 4] 1 shows an SPM image of the surface of Example 1. [Diagram 5] 11 is a cross-sectional CT image of Example 2. [Figure 6] 13 is a cross-sectional CT image of Example 3. [Figure 7] 13 is an SPM image of the surface of Example 3. [Figure 8] 13 is a cross-sectional CT image of Example 4. [Figure 9] 13 is a cross-sectional CT image of Example 5. [Figure 10]13 is a cross-sectional CT image of Example 6. [Figure 11] 13 is a cross-sectional CT image of Example 7. [Figure 12] 1 is a cross-sectional CT image of Comparative Example 1. [Figure 13] 11 is a cross-sectional CT image of Comparative Example 2. [Figure 14] 1 is an SPM image of the surface of Comparative Example 2. [Figure 15] 13 is a cross-sectional CT image of Comparative Example 3. [Figure 16] 13 is a cross-sectional CT image of Comparative Example 4. [Figure 17] 11 is a cross-sectional CT image of Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings.
[0010] Fig. 1 is an explanatory diagram showing a schematic diagram of a porous resin molded body according to the present embodiment, and Fig. 2 is an explanatory diagram showing a manufacturing example of a porous resin molded body according to the present embodiment. As shown in these figures, the porosity of the porous resin molded body 1 changes gradually in one direction of the thickness direction.
[0011] In this embodiment, the porous resin molded body 1 uses polyolefin resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), homopolypropylene (hPP), etc. as a base resin. These resins are appropriately blended together to form the porous resin molded body 1. 13 The propylene fraction of the monomer unit ratio measured by CNMR is less than 14 mol%, 13 The number of tertiary carbons measured by CNMR is adjusted to be 7 or more per 1000 carbon atoms. The porous resin molded body 1 made of the base resin thus adjusted can have a good gradient foam structure in which preferably 50% or more of the pores, more preferably 90% or more of the pores are formed as independent pores, and this will be described later.
[0012] The porous resin molded body 1 can be produced, for example, by preparing a foaming agent-impregnated molded body 2 impregnated with a foaming agent and subjecting it to gradient foaming. The foaming agent-impregnated molded body 2 is preferably in the form of a sheet having a thickness of preferably 0.3 to 10 mm, more preferably 0.5 to 3 mm, but is not limited thereto. Depending on the application of the porous resin molded body 1, it can also be molded into a film having a thickness thinner than the above range, or into a plate having a thickness thicker than the above range.
[0013] The foaming-agent-impregnated molded body 2 can be produced, for example, by dissolving a foaming agent in a base resin melted and kneaded in a plasticizing unit of an injection molding machine, injection-molding the base resin into a predetermined shape while applying a holding pressure to suppress foaming, and removing the base resin from the mold after cooling to a temperature at least lower than the cooling and solidifying temperature of the base resin. Alternatively, the foaming-agent-impregnated molded body 2 may be produced, for example, by preforming the base resin into a predetermined shape, putting the preform into an autoclave, and dissolving the foaming agent in the base resin under high pressure.
[0014] Examples of the foaming agent include physical foaming agents such as carbon dioxide and nitrogen, organic pyrolysis type chemical foaming agents such as azodicarbonamide, or inorganic pyrolysis type chemical foaming agents such as sodium bicarbonate, as well as thermally expandable capsules containing a foaming component. However, the foaming agent can be appropriately selected without being limited to these, depending on the solubility in the base resin, etc.
[0015] When producing the porous resin molded body 1, the foaming agent-impregnated molded body 2 does not have to be prepared in a state in which foaming is completely suppressed. In the process of producing the foaming agent-impregnated molded body 2, a small amount of foaming may occur, resulting in a microfoamed state. As long as foaming is suppressed to an extent that gradient foaming can be controlled as described below, the foaming agent-impregnated molded body 2 may be in an unfoamed or microfoamed state.
[0016] To cause the foaming agent-impregnated molded body 2 to undergo gradient foaming, for example, as shown in FIG. 2, the foaming agent-impregnated molded body 2 molded into a predetermined shape is placed on a mounting table 10, and radiant heat is irradiated toward the foaming agent-impregnated molded body 2 from a heat source 20 disposed above the mounting table 10. This heats the foaming agent-impregnated molded body 2, and foaming begins at the heated portion. At this time, the size and number of the bubbles C change so that they are relatively large on the high-temperature side close to the heat source 20 and relatively small on the low-temperature side far from the heat source 20. As a result, gradient foaming can be advanced so that the porosity changes gradiently in one direction in the thickness direction according to the temperature gradient in the thickness direction.
[0017] When the foaming agent-impregnated molded body 2 is subjected to tilt foaming, it is preferable to restrain one side of the opposing main surfaces of the foaming agent-impregnated molded body 2 (the side in contact with the mounting table 10 in the illustrated example). In the illustrated example, the one side is restrained by carving a suction groove 11 in the top surface of the mounting table 10 according to the shape and size of the foaming agent-impregnated molded body 2 and vacuum-suctioning the entire periphery of the foaming agent-impregnated molded body 2 by the vacuum pump P, but the present invention is not limited to this. If one side of the opposing main surfaces of the foaming agent-impregnated molded body 2 can be restrained so that the movement of the foaming agent-impregnated molded body 2 in the surface direction (direction perpendicular to the thickness direction) is restricted, for example, the foaming agent-impregnated molded body 2 may be peelably adhered to the top surface of the mounting table 10.
[0018] When the inclined foaming is allowed to proceed with one of the opposing main surfaces of the foaming-agent-impregnated molded body 2 being constrained and the other being unconstrained, the shape change due to the inclined foaming is prioritized in the thickness direction. This allows the inclined foaming to be controlled so that the bubbles extend in the thickness direction while suppressing the growth of the bubbles in the surface direction. As a result, it becomes difficult for undulations or wrinkles to occur during the inclined foaming process, and it becomes possible to produce a porous resin molded body 1 with good planarity. In this case, it is preferable to control the inclined foaming so that the cross-sectional shape of the independent pores is preferably circular or elliptical, more preferably elliptical with a major axis in the thickness direction.
[0019] Furthermore, when heating the foaming-agent-impregnated molded body 2, it is preferable to selectively heat the area other than the peripheral edge of the foaming-agent-impregnated molded body 2. To achieve this, for example, as shown in Fig. 2, a shielding member 30 may be provided around the heat source 20 to appropriately adjust the irradiation range of the radiant heat from the heat source 20.
[0020] In this way, the peripheral portion of the foaming-agent-impregnated molded body 2 can be a non-foamed portion that remains unfoamed, or a low-foamed portion (including very low-foamed portion) that has unexpectedly foamed due to heat conduction from the heated portion. As a result, the heated portion of the foaming-agent-impregnated molded body 2 is surrounded by non-foamed or low-foamed portions, and the inclined foaming proceeds in a state of being more constrained in the planar direction, so that the shape change due to the inclined foaming is prioritized in the thickness direction. As a result, the growth of bubbles in the planar direction is more suitably suppressed, and it is possible to control the inclined foaming so that undulations and wrinkles are less likely to occur, and the planarity of the manufactured porous resin molded body 1 can be improved.
[0021] In the illustrated example, radiant heat is irradiated from the heat source 20 arranged on the other of the opposing main surfaces of the foaming-agent-impregnated molded body 2 toward the foaming-agent-impregnated molded body 2 to heat only the other side, but it is also possible to heat or cool the foaming-agent-impregnated molded body 2 from the side of the mounting table 10 by disposing, for example, a resistance heating element or a temperature control circuit in which a temperature control medium circulates inside the mounting table 10. In this way, the adjustable range of the temperature difference between the main surfaces can be made wider.
[0022] In addition, it is preferable to adjust the temperature difference between the principal surfaces so that foaming does not occur in the surface layer portion on one side (low temperature side) of the opposing principal surfaces of the foaming-agent-impregnated molded body 2. This forms a non-foamed layer in the surface layer portion on that side, making it more difficult for swells and wrinkles to occur as the inclined foaming progresses, and making it possible to manufacture a porous resin molded body 1 with better flatness.
[0023] After gradient foaming at the desired bubble ratio, the process is terminated by cooling and solidifying to stop the bubble growth. However, after cooling and solidifying to stop the bubble growth, the porous resin molding 1 can be further processed into a product shape by, for example, thermoforming or the peripheral portions can be trimmed depending on the application of the porous resin molding 1.
[0024] In forming a gradient foam structure in the porous resin molding 1 while controlling gradient foaming as described above, the viscoelastic behavior of the base resin significantly affects the formation of the gradient foam structure. For example, when a polyethylene resin is heated from a temperature below its melting point, its elastic modulus (storage modulus) drops rapidly at temperatures higher than its melting point, and therefore bubbles are broken with even a slight increase in temperature, making it difficult to satisfactorily form a gradient foam structure.
[0025] Therefore, in order to enable the base resin to exhibit good viscoelastic behavior over the temperature range in which gradient foaming progresses, the inventors attempted to blend the above-mentioned polyolefin resins, which have relatively low melting points such as LDPE (melting point: 100 to 115°C) and LLDPE (melting point: 122 to 124°C), as low-melting-point components, with HDPE (melting point: 130 to 137°C) and hPP (melting point: 160 to 165°C), as high-melting-point components, and to examine the viscoelastic behavior of the blended components.
[0026] The low melting point components LDPE and LLDPE have many branches in their molecular chains, and because the entanglement of the molecular chains results in a relatively high melt tension when melted, they are blended with the assumption that they will foam in the molten state.The high melting point components HDPE and hPP have excellent crystallinity and exhibit strain hardening properties, so they are blended with the assumption that they will foam in the solid state.
[0027] By blending these as low-melting and high-melting components, it is expected that the blend will show good viscoelastic behavior over the temperature range in which gradient foaming progresses. However, gradient foaming was inhibited when the proportion of hPP as the high-melting component increased. This is thought to be due to the fact that compatibility with LDPE and LLDPE as low-melting components decreases, which makes bubbles more likely to break at the interface of the sea-island structure. Gradient foaming was also inhibited when the proportion of HDPE as the high-melting component increased. This is thought to be due to the fact that as the proportion of HDPE as the high-melting component increases, the melt tension decreases when the proportions of LDPE and LLDPE as low-melting components decrease, which places a large load on the crystalline components that cannot follow the deformation during foaming.
[0028] In view of this tendency, the present inventors have conducted extensive research focusing on the proportion of polypropylene contained in the base resin and the number of branches of the resin contained in the base resin, i.e., the number of tertiary carbons to which branched chains are bonded. 13 The propylene fraction of the monomer unit ratio measured by CNMR is less than 14 mol%, 13 It was confirmed that a good gradient foam structure can be formed by appropriately selecting low-melting point components and high-melting point components and appropriately adjusting the blending ratio of these components so that the number of tertiary carbons measured by CNMR is 7 or more per 1,000 carbon atoms.
[0029] In order to form a better gradient foam structure, the base resin forming the porous resin molding 1 is preferably a polyethylene resin. More specifically, it is preferable to prepare the porous resin molding 1 so that it contains at least one of LDPE and LLDPE as a low melting point component and HDPE as a high melting point component, but other resin components may be contained within a range that allows a good gradient foam structure to be formed. The base resin may be a copolymer based on these polyethylene resins.
[0030] In addition, within the resin temperature range of 80 to 120°C where foaming phenomenon begins, if the storage modulus is extremely low, the cells will break, whereas if the storage modulus is extremely high, foaming will not occur and heating to near the melting point will be necessary. Considering this, the base resin forming the porous resin molding 1 preferably has a storage modulus of 10 to 120 MPa at 100°C as measured by dynamic viscoelasticity measurement.
[0031] Furthermore, in order to prevent a dramatic drop in elastic modulus due to melting in the resin temperature range of 80 to 120°C where foaming begins to occur, the base resin forming the porous resin molding 1 preferably has a melting peak at or above 120°C in the first DSC curve obtained by differential scanning calorimetry at 10°C / min, and the heat of fusion calculated from the area of the melting peak is preferably 10 J / g or more. EXAMPLES
[0032] The present invention will now be described in more detail with reference to specific examples.
[0033] [Example 1] A base resin having the following composition was used, and nitrogen was dissolved therein as a foaming agent to prepare a foaming-agent-impregnated molded body injection molded into a sheet having a length of 90 mm, a width of 90 mm and a thickness of 1.25 mm. ·LLDPE (MFR (190℃) 3.6g / 10min (ASTM D-1238), density 0.885g / cm 3 (ASTM D-1505)): 50% by weight ·HDPE (MFR (190℃) 12g / 10min (JIS K6922-2), density 0.960g / cm 3 (JIS K7112)): 50% by weight
[0034] Next, the foaming agent-impregnated molded body was placed on a flat mounting table, and the entire periphery of the foaming agent-impregnated molded body was vacuum-suctioned to restrain one of the opposing main surfaces of the foaming agent-impregnated molded body that was in contact with the mounting table. Next, radiant heat was irradiated toward the foaming agent-impregnated molded body from a heat source arranged on the other of the opposing main surfaces of the foaming agent-impregnated molded body, and the foaming agent-impregnated molded body was heated so that there was a temperature difference between the main surfaces. This allowed the inclined foaming to proceed, and then the foaming agent-impregnated molded body was cooled and solidified to stop the growth of bubbles.
[0035] The cross-sectional CT image of the gradient foam molded product thus produced is shown in Figure 3. The CT image confirms that a good gradient foam structure has been formed. In addition, the SPM image of the surface of the gradient foam molded product is shown in Figure 4, and no sea-island structure was observed. The CT images were taken using a Tesco TXS90-ACTIS with a field of view of 4 mm in diameter. The SPM images were taken using a Hitachi High-Tech AFM5300E with a field of view of 20 μm × 20 μm, a scanning speed of 2 to 20 μm / sec, a cantilever spring constant of 2 N / m, and a phase mode (PM) field of view.
[0036] <Dynamic viscoelasticity measurement> A test piece was cut out from the produced gradient foam molded article and subjected to dynamic viscoelasticity measurement, and the storage modulus at 100°C was found to be 49 MPa. The dynamic viscoelasticity measurement was performed using a measuring device, DMS6100, manufactured by Seiko Instruments Inc. The temperature rise rate was set to 3° C. / min, and the measurement was performed with a strain amplitude of 10 μm, a tensile / compressive force gain of 1.2, and a frequency of 1 Hz.
[0037] < 13 CNMR measurement> A test piece is cut out from the produced gradient foam molded article to prepare a sample. 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and it was found that no propylene was detected and the number of tertiary carbons per 1000 carbon atoms was 27.2. 13The CNMR measurement was performed using a JNM-ECA made by JEOL Ltd. The measurement temperature was 130°C, and the number of accumulations was 10,000. The sample solvent was benzene-d6 / ortho-dichlorobenzene-d4 = 1 / 3 (v / v), and was adjusted to 60 mg sample / 600 μL. Quantitative method for monomer components The ethylene / propylene monomer ratio of the polyolefin component was determined by the following formula: E=k{1 / 2(S βδ +S δδ +S αγ +S αδ )+1 / 4(S γδ )} P=k{S αα +1 / 2(S αγ +S αδ )} Propylene ratio (mol%) = P / (P+E) Quantitative method for tertiary carbon 13 The percentage of tertiary carbon was calculated by dividing the total integral value T of the peaks derived from the four tertiary carbons shown below among the carbon peaks obtained by CNMR by the sum of the total peaks derived from the main chain backbone and side chain carbons having secondary or lower carbon atoms and T. T δδ (Butene)=T δδ (B): 39.8 ppm T δδ (Hexene)=T δδ (H): 38.3 ppm T βδ (Propylene)=T βδ (P): 31 ppm T ββ (Propylene)=T ββ (P): 28.9 ppm T=T δδ (B)+T _δδ (H)+T βδ (P)+T ββ (P)
[0038] <Differential scanning calorimetry> A test piece was cut out from the produced gradient foamed molded product and subjected to differential scanning calorimetry. In the first DSC curve obtained by differential scanning calorimetry at 10°C / min, a melting peak appeared at 129.5°C. The heat of fusion at 120°C or higher, calculated from the area of the melting peak, was 72.2 J / g. Differential scanning calorimetry was performed using a TA Instruments Discovery DSC2500 measurement device at 10°C / min in the range of 0°C to 200°C. The melting enthalpy at 120°C or higher was calculated by connecting two points from 120°C to the temperature where the melting peak returns to the baseline with a straight line to form a reference line, and the area value with respect to the spectrum was used.
[0039] [Example 2] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. LLDPE (same as in Example 1): 70% by weight HDPE (same as in Example 1): 30% by weight
[0040] A gradient foamed molded product was produced in the same manner as in Example 1, except that the amount of heat used for heating the foaming agent-impregnated molded product was 0.75 times that of Example 1. A CT image of the cross section is shown in Figure 5. From this CT image, it can be confirmed that a good gradient foam structure was formed.
[0041] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 17 MPa.
[0042] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and it was found that no propylene was detected and the number of tertiary carbons per 1000 carbon atoms was 35.8.
[0043] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak appeared at 128.5° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak was 45.1 J / g.
[0044] [Example 3] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. ·LDPE (MFR (190℃) 23g / 10min (JIS K6922-2), density 0.918g / cm 3 (JIS K7112)): 50% by weight HDPE (same as in Example 1): 50% by weight
[0045] In addition, a gradient foam molded product was produced by heating the foaming agent-impregnated molded product in the same manner as in Example 1. A CT image of the cross section is shown in Figure 6. This CT image confirms that a good gradient foam structure was formed. In addition, an SPM image of the surface of the gradient foam molded product is shown in Figure 7, and no sea-island structure was observed.
[0046] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 69 MPa.
[0047] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and it was found that no propylene was detected and the number of tertiary carbons per 1000 carbon atoms was 9.0.
[0048] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak appeared at 129.6° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak was 77.3 J / g.
[0049] [Example 4] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. LLDPE (same as in Example 1): 47.5% by weight HDPE (same as in Example 1): 47.5% by weight ·hPP(MFR(230℃)13g / 10min(JIS K6921-2), density 0.9g / cm 3 (JIS K6921-2)): 5% by weight
[0050] In addition, the foaming agent-impregnated molded article was heated to produce a gradient foamed molded article in the same manner as in Example 1. A CT image of the cross section is shown in Figure 8. From this CT image, it can be confirmed that a good gradient foam structure was formed.
[0051] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 57 MPa.
[0052] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and the propylene fraction was 4.6 mol %, and the number of tertiary carbons per 1000 carbon atoms was 43.7.
[0053] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak derived from PE appeared at 129.2° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak derived from PE was 61.6 J / g.
[0054] [Example 5] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. LLDPE (same as in Example 1): 45% by weight HDPE (same as in Example 1): 45% by weight hPP (same as in Example 4): 10% by weight
[0055] In addition, the foaming agent-impregnated molded article was heated to produce a gradient foamed molded article in the same manner as in Example 1. A CT image of the cross section is shown in Figure 9. From this CT image, it can be confirmed that a good gradient foam structure was formed.
[0056] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 61 MPa.
[0057] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and the propylene fraction was found to be 7.9 mol %, and the number of tertiary carbons per 1000 carbon atoms was found to be 61.3.
[0058] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak derived from PE appeared at 129.1° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak derived from PE was 56.5 J / g.
[0059] [Example 6] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. LLDPE (same as in Example 1): 49.5% by weight HDPE (same as in Example 1): 49.5% by weight Additive (Mitsubishi Chemical Corporation: Metablen MZE-4): 1% by weight
[0060] The foaming agent-impregnated molded article was heated to produce a gradient foamed molded article in the same manner as in Example 1. A CT image of the cross section is shown in Figure 10. From this CT image, it can be confirmed that a good gradient foam structure was formed.
[0061] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 57 MPa.
[0062] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and it was found that no propylene was detected and the number of tertiary carbons per 1000 carbon atoms was 24.9.
[0063] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak appeared at 130.2° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak was 75.6 J / g.
[0064] [Example 7] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. LLDPE (same as in Example 1): 47.5% by weight HDPE (same as in Example 1): 47.5% by weight Additive (Mitsubishi Chemical Corporation: Metablen MZE-4): 5% by weight
[0065] The foaming agent-impregnated molded article was heated to produce a gradient foamed molded article in the same manner as in Example 1. A CT image of the cross section is shown in Figure 11. From this CT image, it can be confirmed that a good gradient foam structure was formed.
[0066] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 48 MPa.
[0067] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and it was found that no propylene was detected and the number of tertiary carbons per 1000 carbon atoms was 24.3.
[0068] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak appeared at 129.7° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak was 70.6 J / g.
[0069] [Comparative Example 1] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. HDPE (same as in Example 1): 100% by weight
[0070] A gradient foamed molded product was produced in the same manner as in Example 1, except that the amount of heat used to heat the foaming agent-impregnated molded product was doubled. A CT image of the cross section is shown in Figure 12. From this CT image, it can be confirmed that the bubbles have been broken and a gradient foam structure has not been formed.
[0071] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 232 MPa.
[0072] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and neither propylene nor tertiary carbons were detected.
[0073] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak appeared at 130.6° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak was 122.6 J / g.
[0074] [Comparative Example 2] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. LLDPE (same as in Example 1): 50% by weight hPP (same as in Example 4): 50% by weight
[0075] A gradient foam molded product was produced in the same manner as in Example 1, except that the amount of heat was 0.25 times that of the foaming agent-impregnated molded product when it was heated. A CT image of the cross section is shown in FIG. 13. From this CT image, it can be confirmed that the bubbles have been broken and no gradient foam structure has been formed. Furthermore, an SPM image of the surface of the gradient foam molded product is shown in FIG. 14, and a sea-island structure that is thought to be a phase separation of LLDPE and hPP was observed.
[0076] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 140 MPa.
[0077] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and the propylene fraction was 44.4 mol %, and the number of tertiary carbons per 1000 carbon atoms was 200.9.
[0078] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak derived from PP appeared at 166.9° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak was 45.3 J / g.
[0079] [Comparative Example 3] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. LDPE (Novatec LD LJ8041, manufactured by Japan Polyethylene Co., Ltd.): 40% by weight HDPE (Novatec HD HJ580N, manufactured by Japan Polyethylene Corporation): 60% by weight
[0080] A gradient foamed molded product was produced in the same manner as in Example 1, except that the amount of heat used to heat the foaming agent-impregnated molded product was 1.5 times that of Example 1. A CT image of the cross section is shown in Figure 15. From this CT image, it can be seen that the bubbles have been broken and a gradient foam structure has not been formed.
[0081] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 94 MPa.
[0082] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and it was found that no propylene was detected and the number of tertiary carbons per 1000 carbon atoms was 6.5.
[0083] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak appeared at 131.4° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak was 84.3 J / g.
[0084] [Comparative Example 4] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. LDPE (same as in Example 3): 30% by weight HDPE (same as in Example 1): 70% by weight
[0085] A gradient foamed molded product was produced in the same manner as in Example 1, except that the amount of heat used to heat the foaming agent-impregnated molded product was 1.5 times that of Example 1. A CT image of the cross section is shown in Figure 16. From this CT image, it can be seen that the bubbles have been broken and a gradient foam structure has not been formed.
[0086] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 121 MPa.
[0087] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and it was found that no propylene was detected and the number of tertiary carbons per 1000 carbon atoms was 6.3.
[0088] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak appeared at 133.1° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak was 42.3 J / g.
[0089] [Comparative Example 5] A foaming agent-impregnated molded body was prepared in the same manner as in Example 1, except that a base resin having the following composition was used. LLDPE (same as in Example 1): 40% by weight HDPE (same as in Example 1): 40% by weight hPP (same as in Example 4): 20% by weight
[0090] In addition, a gradient foamed molded product was produced by heating the foaming agent-impregnated molded product in the same manner as in Example 1. A CT image of the cross section is shown in Fig. 17. From this CT image, it can be confirmed that the bubbles have been broken and a gradient foamed structure has not been formed.
[0091] <Dynamic viscoelasticity measurement> When dynamic viscoelasticity was measured in the same manner as in Example 1, the storage modulus at 100° C. was 104 MPa.
[0092] < 13 CNMR measurement> In the same manner as in Example 1, 13 The monomer unit ratio and the number of tertiary carbons per 1000 carbon atoms were determined by CNMR, and the propylene fraction was found to be 14.2 mol %, and the number of tertiary carbons per 1000 carbon atoms was found to be 86.3.
[0093] <Differential scanning calorimetry> Differential scanning calorimetry was performed in the same manner as in Example 1. In the first DSC curve obtained by differential scanning calorimetry at 10° C. / min, a melting peak derived from PE appeared at 129.2° C. The heat of fusion at 120° C. or higher calculated from the area of the melting peak derived from PE was 50.2 J / g.
[0094] Although the present invention has been described above by showing preferred embodiments, it goes without saying that the present invention is not limited to the above-described embodiments, and various modifications can be made within the scope of the present invention.
[0095] The porous resin molded body according to the present invention can be used in a wide range of applications in various fields. In addition to being applicable to applications such as civil engineering and construction materials, automotive materials, and packaging materials that utilize the properties such as heat insulation, impact absorption, and sound absorption, the porous resin molded body can also be used as a millimeter wave low reflection sheet for improving the stability of a radar system using millimeter waves, for example, by utilizing the fact that the dielectric constant also changes gradually as the porosity changes gradually between the opposing main surfaces. [Explanation of symbols]
[0096] 1. Porous resin molded body
Claims
1. A porous resin molded body, the porosity of which changes gradually in the thickness direction, The base resin is polyolefin resin. The base resin is 13 In the monomer unit ratio measured by CNMR, the propylene fraction is less than 14 mol%, 13 A porous resin molded article, characterized in that the number of tertiary carbon atoms measured by CNMR is 7 or more per 1,000 carbon atoms.
2. 2. The porous resin molded article according to claim 1, wherein 50% or more of the pores are independent pores.
3. 3. The porous resin molded article according to claim 2, wherein the cross-sectional shape of the independent pores is a circle or an ellipse.
4. 3. The porous resin molded article according to claim 2, wherein the cross-sectional shape of each of the independent pores is an ellipse having a major axis in the thickness direction.
5. 2. The porous resin molded body according to claim 1, wherein the base resin has a storage modulus of 10 to 120 MPa at 100° C. as determined by dynamic viscoelasticity measurement.
6. 2. The porous resin molded article according to claim 1, wherein the base resin has a melting peak at 120° C. or higher in a first DSC curve obtained by differential scanning calorimetry at 10° C. / min.
7. 7. The porous resin molding according to claim 6, wherein the heat of fusion calculated from the area of the fusion peak is 10 J / g or more.
8. The porous resin molded body according to any one of claims 1 to 7, wherein the base resin is a polyethylene resin.
9. 9. The porous resin molded article according to claim 8, comprising at least one of a low density polyethylene and a linear low density polyethylene, and a high density polyethylene.
Citation Information
Patent Citations
Plastic sheet foamed in gradient manner and manufacturing method therefor
JP2002363324A